FRI0521 A framework and process to develop core outcome measurement sets for clinical trials in rheumatology: omeract filter 2.0. (23rd January 2014) - Boers, M.; Kirwan, J. R.; Wells, G.; Beaton, D.; Gossec, L.; d'Agostino, M.-A.; Conaghan, P. G.; Bingham, C. O.; Brooks, P. M.; Landewé, R. B. M.; March, L.; Simon, L. S.; et al.
Abstract : Background: Lack of standardization of outcome measures limits the usefulness of clinical trial evidence to advance clinical practice and improve health. Agreement on a core set of outcome measures to be reported in all trials could address this problem. Over the past two decades the Outcome Measures in Rheumatology (OMERACT) international consensus initiative has successfully developed core sets for many rheumatologic conditions but its expanding scope called for clarification and update of its underlying conceptual framework and working process. Objectives: To formulate a conceptual framework for outcome measurement across health conditions in rheumatology and to establish an explicit process to develop core sets. Methods: Literature searches, iterative consensus process (internet-based surveys, small and large group processes) of stakeholders including patients, health professionals and methodologists within and outside rheumatology. Results: The framework comprises three core "Areas": Death, Life Impact and Pathophysiologic Manifestations; with a fourth strongly recommended: Resource Use. The process of core set development for a health condition starts by selecting core Domains within the Areas ('core domain set'). This requires literature searches, involvement of all relevant stakeholders — especially patients — and one or more consensus process. Next, developers select at least one applicable measurement instrument for each core Domain. Applicability means that the instrument must be Truthful (face, content and construct validity), Discriminative (between situations of interest) and Feasible (understandable, acceptable (time and monetary) costs). Depending on the quality of the instruments stakeholders formulate either a preliminary or a final 'core outcome measurement set'. In the OMERACT 11 consensus conference in May 2012, 96% of voting participants (n=125) endorsed the model and process. Conclusions: OMERACT has established a strongly endorsed, generic framework including a process to develop core outcome measurement sets for rheumatology, that is likely to be useful in other areas of health care as well. Acknowledgements: Caroline Terwee, Leanne Idzerda, Reuben Escorpizo, Annelies Boonen, Susan Magasi, Ian Sinha, Paula Williamson, Jane Blazeby, Gerold Stucki who gave valuable advice on this abstract; all survey participants. Disclosure of Interest: None Declared